Sharks : what do great whites, hammerheads, and whale sharks get up to all day? - Jackson, Carlee; Prabhat, Chaaya (London : Neon Squid, 2022)
"An . . . illustrated nonfiction story following great whites, hammerheads, whale sharks, and more over the course of one day"--Provided by publisher.
Includes index.
Booklist
Booklist, May 2022
3.3
K-3.
K-3
Keywords: Sharks -- Juvenile literature; Sharks; Sharks